EFEKTIVITAS MODEL INQUIRY BERBASIS THK DALAM MENINGKATKAN KETERAMPILAN SOSIAL SISWA KELAS V SD N 5 PEDUNGAN TAHUN AJARAN 2024/2025 - Dewi Anzelina, M.Pd.; Ni Kadek Sri Puspayanti; Ni Made Putri Wijayanti; Ni Made Yudhiasari Darma Putri; Ni Made Lisa Aprilia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the low social skills of fifth grade students at SDNegeri 5 Pedungan. The purpose of this study was to determine the effectivenessof implementing the inquiry learning model based on Tri Hita Karana (THK) values,in improving students' social skills. This study uses the Classroom Action Approachwhich is implemented in two cycles, which include the planning, implementation,observation, and reflection stages. Data collection techniques are carried outthrough observation, documentation, and testing. The results of the study showedthat students' social skills increased significantly after the implementation of thelearning model. The conclusion of this study is that inquiry learning based on THKvalues is effective in forming students' character as a whole and improving thequality of social skills in the classroom environment.